Pendampingan Etika Bisnis Syariah dalam Upaya Meningkatkan Daya Saing UMKM di Kebupaten Tangerang - Maskur Rosyid; Eka Pratiwi (ISLAMINOMICS: JOURNAL OF ISLAMIC ECONOMICS, BUSINESS AND FINANCE, 2020)
This study aims to find out how the application of Sharia Business Ethnic for perpetrators UMKM which exists in Kecamatan Panongan, in enhancing the competitivesness of its business which underlies forms and principles contained in Sharia Business Ethich. In the business context, the application of sharia ethics faces obstacles in the form of process, people and technologi and marketing. This study uses qualitative method in which the researcher conducts interviews and direct observations to the perpetratos UMKM. So the results of this study are perpetratos UMKM. The application of sharia business ethics in conducting its business, in order to increase competitiveness or profit in the long run and good will obtained from the image of business from the image of business competitors that are run and can develop in the future, this research can be made into a framework or model for other business actors.